Critical reflections on Ghoreishian’s ‘Gender and Sexual Organs' - Abedinifard, Mostafa (My University, 2013)
This paper is a critical response to Ana Ghoreishian’s essay “Gender and Sexual Organs: Iraj Mirza’s ‘Arif Namah and Hajviyat [plural of hajv, i.e., invective],” and focuses on the gender politics of Iraj Mirza’s most celebrated work, i.e., Aref Nameh. I welcome Ghoreishian’s insight that the critical value of Iraj Mirza’s sexual hajv (i.e., invective satire) should not be overshadowed by moralistic judgements about it. However, I challenge the picture she presents of Aref Nameh’s policy vis-à-vis gender. With this general theme in mind, and to rectify the above picture, I discuss three subjects: the phallocentric language in Aref Nameh, its attitude towards homoeroticism, and its treatment of hejab. First, I argue that while Aref Nameh’s sexual hajv can, as Ghoreishian shows, serve subversive functions in certain socio-political contexts, the poem’s phallocentrism renders it as obviously conservative in regard to gender. In the next part, while taking issue with Ghoreishian’s representation of Aref Nameh as a peril for heteronormativity, I provide further socio-historical context for the poem to suggest that, having been written at a critical juncture in the history of the transformations in Iranian society’s gender order, Aref Nameh was arguably constructed as a pro-modernity narrative that tends to foster the abjection of homoerotic acts and identities. Finally, upon contemplating Aref Nameh’s equating women’s unveiling with emancipation—as mirrored and endorsed in Ghoreishian’s article—my paper shows how the poem reveals significant traces of complicity with its contemporary modern discourse towards women’s veil. This discourse, that considered the heterosocialization of the public space as a sine qua non to Iranian modernity, encouraged the literal unveiling of women while simultaneously subjecting them to a surrogate nexus of internal veils.
Keywords: gender; homoeroticism; satire